2003
DOI: 10.1021/jp022580n
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interactions in Model Charged Polysaccharide Systems

Abstract: Temporary networks were obtained from mixtures of two derivatized chitosans, one with -cyclodextrin (CD) cavities and the other with adamantyl (AD) moieties, randomly distributed along the chains. The viscoelastic response of these original systems in which cyclodextrin-adamantane complexes play a role of interchain junctions (sticky points) was investigated as a function of polymer concentration, degree of modification, ionic strength, temperature, and addition of competitive molecules. In the semidilute regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 23 publications
5
70
0
1
Order By: Relevance
“…While low modification resulted in weak supramolecular networks (typical G' < 100Pa), their results demonstrated the importance of polymer concentration, charge, and competitive binding on network assembly. 62 Moreover, theoretical and experimental approaches have been combined to illustrate the importance of multivalent and inter-polymer interaction to generate high avidity and network stability. [63][64] Toward harnessing this understanding, our group 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 has demonstrated that higher degrees of modification of HA with these same guest-host groups enables formation of more robust supramolecular hydrogels (G' = 10 kPa possible) through generation of larger net avidity between polymers which may be enhanced by multifold polymer junctions.…”
Section: Polymeric Assemblymentioning
confidence: 99%
“…While low modification resulted in weak supramolecular networks (typical G' < 100Pa), their results demonstrated the importance of polymer concentration, charge, and competitive binding on network assembly. 62 Moreover, theoretical and experimental approaches have been combined to illustrate the importance of multivalent and inter-polymer interaction to generate high avidity and network stability. [63][64] Toward harnessing this understanding, our group 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 has demonstrated that higher degrees of modification of HA with these same guest-host groups enables formation of more robust supramolecular hydrogels (G' = 10 kPa possible) through generation of larger net avidity between polymers which may be enhanced by multifold polymer junctions.…”
Section: Polymeric Assemblymentioning
confidence: 99%
“…[38] Driven by hydrophobic and van der Waals interactions, the relatively hydrophobic pocket of bCD serves as a reversible binding site for a wide range of lipophilic molecules (e.g., adamantane and cholesterol). [39][40][41] Reversible hydrogel systems, for example, those composed of adamantane-and bCD-grafted chitosan [42] or hyaluronic acid [33,43] have been described in the literature. Also, stimuli-responsive gels were formed after combining poly(acrylamide) derivatized with either bCD or aromatic guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Huh and co-workers described systems, in which CDs formed inclusion complexes with poly(ethylene oxide)-grafted polysaccharides [30,31]. More recently, supramolecular gel-like networks were obtained by mixing a CD-bearing host polymer and a hydrophobically modified guest polymer [32][33][34][35][36]. Using the same approach, studies were carried out in our laboratory to design a stable dispersion of 200 nm in size nanoassemblies, combining the properties of both polysaccharides and CDs [37].…”
Section: Introductionmentioning
confidence: 99%